lncRNA LOC100911717-targeting GAP43-mediated sympathetic remodeling after myocardial infarction in rats - Li, Pingjiang; Wang, Kang; Yin, Jie; Qi, Lei; Hu, Hesheng; Yang, Peijin; Shi, Yugen; Li, Yan; Feng, Meng; Lyu, Hangji; Ge, Weili; Li, Xiaolu; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective: Sudden cardiac death (SCD) after myocardial infarction (MI) is the result of malignant ventricular arrhythmias (VAs) due to sympathetic remodeling. M1 type macrophages is closely associated with inflammation after MI and sympathetic remodeling. Long non-coding RNAs (lncRNAs) is critical in regulating cardiovascular disease development. This study aims to identify lncRNAs involved in MI and reveal the possible mechanism. Methods and results: We selected M0 type and M1 type macrophages for sequencing and screened them for differentially expressed lncRNAs. We found that lncRNA 100911717 was upregulated in M1 type macrophages compared with M0 type and was also upregulated in MI heart tissues. Furthermore, we performed RNA pull-down and found the lncRNA LOC100911717 could interact with GPA43. In addition, we found that the expression of GAP43 was suppressed and the incidence of VAs was reduced after knockdown of lncRNA LOC100911717 in rat hearts with adeno-associated virus (AAV), as determined via immunofluorescence assays and programmed electrical stimulation. Conclusions: Our study may reveal a novel relationship between lncRNA LOC100911717 and GAP43. After MI, lncRNA LOC100911717 was up-regulated and enhanced the expression of GAP43 then increasing the sympathetic remodeling and VAs events. Silencing the lncRNA LOC100911717 could reduce the sympathetic remodeling and VAs.